Comparison of androgen receptor mutation detection between plasma extracellular vesicle DNA and cell-free DNA and its relationship to prostate cancer prognosis - Ting Ding; Xiao Li; Longlong Zhang; Zhen Wei; Chaoliang Xiong; Hong Wang; Xiaoke Hao; Xianfei Zeng (Annals of Medicine)
Background In liquid biopsy, mutation detection is primarily performed using cell-free DNA (cfDNA). However, the numerous advantages of extracellular vesicle (EV) DNA for mutation detection have gradually garnered the attention of researchers in recent years. This study aimed to compare the differences between EV DNA and cfDNA in mutation detection and explore the role of plasma androgen receptor (AR) mutations in the prognosis of prostate cancer (PCa).Methods We compared the biological characteristics of plasma extracellular vesicle DNA (p-EV DNA) and cfDNA by capillary electrophoresis and concentration detection. Subsequently, we performed pan-oncogene-targeted sequencing in paired tissue and plasma samples from five patients with PCa to verify the feasibility of mutation detection using p-EV DNA and cfDNA. Further, we conducted AR mutation detection in expanded samples to compare the differences between EV DNA and cfDNA in mutation detection and to analyse their role in PCa.Results p-EV DNA fragments were larger than plasma cell-free DNA (p-cfDNA) fragments; however, there was no significant difference in their concentrations in the plasma of patients with PCa. Feasibility analysis revealed that major mutations associated with PCa detected in tissue samples could be identified in both p-EV DNA and p-cfDNA. Advantage comparison found that, although cfDNA could detect more mutations, AR mutations in EV DNA were more strongly associated with a poor prognosis of PCa than cfDNA.Conclusion Mutation detection using either EV DNA or cfDNA is both feasible in PCa liquid biopsies, and EV DNA AR mutations have an advantage in prognostic assessment for PCa. This study lays the foundation for future research on EV DNA-related biomarkers.